1980
DOI: 10.1103/physrevlett.45.266
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of High-Frequency Sound Propagation inHe3-B

Abstract: Measurements of the attenuation and velocity of pulsed high-frequency sound have been performed up to 133 MHz in superfluid 3 He-Z?. A new collective mode of the order parameter was discovered at a frequency extrapolated to T c of oo = (1.165 ± 0.05)A K:s (T c ), where ABC S (T) is the energy gap in the weak-coupling BCS theory. The group velocity has been observed to decrease by as much as | of the zero-sound velocity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
28
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(30 citation statements)
references
References 8 publications
2
28
0
Order By: Relevance
“…7 ' 8 At a given pressure, v g vs a> can be fitted by least squares to yield o) sq and A sq . Our results are a; sq /A BCS (0) = 1.501 ±0.003 and A sq (0) = 0.010 (4) ±0.001 at a pressure of 13.1 bars. A BCS (T) is taken from numerical calculations.…”
supporting
confidence: 44%
See 1 more Smart Citation
“…7 ' 8 At a given pressure, v g vs a> can be fitted by least squares to yield o) sq and A sq . Our results are a; sq /A BCS (0) = 1.501 ±0.003 and A sq (0) = 0.010 (4) ±0.001 at a pressure of 13.1 bars. A BCS (T) is taken from numerical calculations.…”
supporting
confidence: 44%
“…4 In order to take data we cooled the 3 He at a pressure in the interval 11.7 to 15.5 bars to a minimum temperature T/T c ^ 0.2 and allowed it to slowly warm up through the superfluid over a period of several days. The received acoustic pulses at frequencies of 12.06, 36.33, 60.56, 84.83, 109.10, and 133.33 MHz were signal averaged and the peaks were fitted to Gaussians.…”
mentioning
confidence: 99%
“…1 we plot^2 + (T) for the two extreme cases jF 2 a =0, x 3~1 = -0A32 (hereafter case I) and F 2 a = -1.56, j^" 1 = 0 (hereafter case II) corresponding to co 2+ (0) = 1.075A BCS (0), with A BCS (T) the weak-coupling BCS energy gap. 6 For comparison we also show the "bare"g factors calculated for F 2 3 ' a = x 3 -1 = 0. If we take A(T) = A BCS( T ), then f°r f ix ed values of F Q a , F 2 s * a , and x 3 , g 2± and ct> L are universal functions of T/T c , as are to 2± (T)/A(T) and dco 2± /dT.…”
Section: *-»£('-£^M(»ek-mentioning
confidence: 99%
“…The Zeeman splitting of the 2 -mode has yet to be observed, but the splitting of the 2 + mode has been measured by Avenel, Varoquaux, and Ebisawa; 4 their observation of a fivefold splitting of the new ultrasonic absorption line discovered by Giannetta et al 5 and Mast et al 6 established conclusively that this absorption line is associated with the 2+ mode. Equation (2) gives 6oo(T,H), the linear splitting of the modes at a fixed temperature, but experimentally one measures 6T(w, H), the splitting in temperature of the modes at a fixed frequency.…”
mentioning
confidence: 95%
“…Indeed ultra-sound absorption spectroscopy provided the first detection of the Higgs mode in a BCS condensate. 59,60 The definitive identification of the absorption resonance as the J c = 2 + Higgs mode was made by Avenel et al who observed the five-fold Zeeman splitting of the zero-sound absorption resonance in an applied magnetic field. 61 Acoustic spectroscopy provides precision measurements of the mass of the J c = of the masses of the J c = 2 ± modes using longitudinal and transverse sound spectroscopy, combined with measurements of the velocities of zero-sound, first-sound, and the magnetic susceptibilties in both the normal-and superfluid phases of 3 He.…”
Section: (−)mentioning
confidence: 99%